Fluoroscopy Assisted Minimally Invasive Transplantation of Allogenic Mesenchymal Stromal Cells Embedded in HyStem Reduces the Progression of Nucleus Pulposus Degeneration in the Damaged Interverbal Disc: A Preliminary Study in Rabbits. (30th March 2014) - Subhan, Rifa Aquidah; Puvanan, Karunanithi; Murali, Malliga Raman; Balaji Raghavendran, Hanumantha Rao; Shani, Samuel; Abdullah, Basri Johan Jeet; Amir Abbas, Azlina; Mohamed, Jamal Azmi; Kamarul, Tunku
Abstract : This study was conducted to develop a technique for minimally invasive and accurate delivery of stem cells to augment nucleus pulposus (NP) in damaged intervertebral discs (IVD). IVD damage was created in noncontiguous discs at L4-L5 level; rabbits (N = 12 ) were randomly divided into three groups: group I treated with MSCs in HyStem hydrogel, group II treated with HyStem alone, and group III received no intervention. MSCs and hydrogel were administered to the damaged disc under guidance of fluoroscopy. Augmentation of NP was assessed through histological and MRI T2 mapping of the NP after eight weeks of transplantation. T2 weighted signal intensity was higher in group I than in groups II and III (P < 0.05 ). Disc height index showed maximum disc height in group I compared to groups II and III. Histological score of the degenerative index was significantly (P < 0.05 ) lower in group I (8.6 ± 1.8) than that in groups II (11.6 ± 2.3) and III (18.0 ± 5.7). Immunohistochemistry staining for collagen type II and aggrecan staining were higher in group I as compared to other groups. Our results demonstrate that the minimally invasive administration of MSCs in hyaluronan hydrogel (HyStem) augments the repair of NP in damaged IVD.